Functionalization of yogurts with Agaricus bisporus extracts microencapsulated through the spray-drying technique - Heleno, Sandrina A. (2018)
The extensive use of synthetic additives by the food industry, some of them recognized as carcinogenic substances, has alerted consumers towards the need of adopting healthier habits. Thus, their appetence for functional foods, i.e. foods promoting positive effects on health in addition to their basic nutritional purposes, is progressively increasing. Moreover the food industry has been under high pressure due to legislation restrictions concerning the use of some of these artificial additives. Mushroom extracts contain bioactive compounds potentially useful to functionalize foodstuffs. In fact, functional foods are integrating the daily diet of consumers and are gaining prominence worldwide. Agaricus bisporus is the species with the highest consumption worldwide, showing a great potential to be used to enrich food matrices, mainly due to its high amount of ergosterol. In the present work, alcoholic extracts of A. bisporus were studied for their bioactivity and viability as functional ingredients in a food product with high water content (yogurt). Extracts were microencapsulated by spray-drying (to improve their stability and hydrophilicity), using maltodextrin crosslinked with citric acid as the encapsulating material. The effect of thermal treatment (after atomization) on crosslinking and bioactivity of the produced microspheres was tested. The incorporation of free and thermally untreated forms resulted in yogurts with higher initial antioxidant activity (EC50 values: 214 and 272 mg/mL) that decreased after 7 days (EC50 values: 248 and 314 mg/mL). Contrarily, thermally treated microencapsulated extracts showed higher antioxidant activity after the same period (EC50 values, 0 days: 106 mg/mL; 7 days: 48.7 mg/mL), in result of an effective protection provided by microencapsulation with crosslinked maltodextrin and citric acid. Functionalized yogurts showed an overall maintenance of nutritional properties.